The Correlation Between Cognitive Function with the Quality of Life in the Elderly in Barusari Village South Semarang District - Dwi Nur Aini (Jurnal Keperawatan, 2016)
The problem faced by the elderly as human aging process is a process and natural. Some problems and disorders that frequently arise or occur in the elderly is declining cognitive function. Cognitive decline in the elderly is usually preceded by decline of memory or memory (forgetfulness) and other cognitive mengggu real life activities. The purpose of this study was to find out: "The correlation between cognitive function and quality of life in the elderly (60-74 years) in Barusari Vilage of South Semarang. This research is a descriptive correlative with cross sectional design. The population in this study is that all elderly people aged 60-74 years.The sampling technique used is total sampling. Bivariate test using chi square test. The results showed that the cognitive function of elderly most categories of serious disturbance (48.1%), and most of the quality of life category is independently as many as 32 people (61.5%). Statistical test results found there is significant correlation between cognitive function and quality of life in the elderly (60-74 years) in Barusari Vilage of South Semarang with p value of 0.000.Based on the results of the study are expected to nursing profession are expected to provide nursing assistance to the elderly who have suffered physical setbacks by helping in order to keep good quality of life and help in order to have good cognitive abilities.